To multiply the polynomial expressions \( (x + 2)(x - 4) \), we can use the distributive property (also known as the FOIL method for binomials):
\[ (x + 2)(x - 4) = x \cdot x + x \cdot (-4) + 2 \cdot x + 2 \cdot (-4) \]
Now, let's perform the multiplication:
- \( x \cdot x = x^2 \)
- \( x \cdot (-4) = -4x \)
- \( 2 \cdot x = 2x \)
- \( 2 \cdot (-4) = -8 \)
Now, combine these results:
\[ x^2 - 4x + 2x - 8 \]
Next, combine like terms \(-4x\) and \(2x\):
\[ x^2 + (-4x + 2x) - 8 = x^2 - 2x - 8 \]
Thus, the answer can be expressed in the form:
\[ x^2 + (-2)x + (-8) \]
Filling in the blanks, we have:
\[ \text{} x^2 + \text{} x + \text{__} \rightarrow 1, -2, -8 \]
So the completed expression is:
- \(1\)
- \(-2\)
- \(-8\)
Final answer: \( x^2 + (-2)x + (-8) \) or \( x^2 - 2x - 8 \).